Analisis Kualitas Produk Di Bisa Group (SUSHI TEI) Medan - Indra (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
BISA Group – Medan is a company engaged in the food and beverage sector. This company was founded in 2004 which is located on Jl. Teuku Daud No. 9, Madras Hulu, Kec. Medan Polonia, Medan City, North Sumatra. According to(Kotler, Philip & Amstrong, 2020),product quality is a strategic weapon with the capacity to beat competitors. So only companies with the best product quality will grow rapidly, and in the long run the company will be more successful than other companies. other. The research method used in this research is descriptive qualitative method. Sources of data used are primary and secondary data sources. Analysis of the data used is Miles and Huberman. The credibility test of the data used is source triangulation. The results of the research are: 6 dimensions of product quality where all dimensions produce good results, but there are some that can be given input so that the company can develop in a better direction. The suggestions are that the company does not only develop a service system, but also better facilities and infrastructure to be developed so as not to make customers queue for too long, improve quality control so that there is no damage to the products served to customers, given the opportunity for customers to provide input on new products. , as well as giving advance warning about damage that could cause a lot of loss, without having to burden employees